Plankton Community Structure and Water Environment Conditions in The Pelintung Industry Area, Dumai - Nurrachmi, Irvina; Amin, Bintal; Siregar, Sofyan Husein; Galib, Musrifin (Journal of Coastal and Ocean Sciences, 2021)
This research was conducted in July 2020 in Pelintung Industrial Area Waters, Dumai City, Riau Province. The purpose of this study was to determine the community structure of phytoplankton and zooplankton and the condition of their aquatic environment. The method used in this research is a survey method. The phytoplankton community structure shows H 'values ​​ranging from 3.62 to 4.02, E values ​​ranging from 0.78 to 0.85. and C values ​​ranged from 0.08 to 0.12 while the zooplankton community structure values ​​for H 'values ​​ranged (0.0000 - 2.2140, E values ​​ranged (E) (0.0000 - 0.6665), and C values ​​ranged (0.2325 - 1.0000) For the abundance of phytoplankton 18.90 ind / L - 55.56 ind / L and zooplankton 10.29 - 23.05 ind / L, this value shows that the waters of the Pelintung industrial area are still relatively good, not yet polluted from being able to support biota. Nitrate concentrations in these waters range from 0.096 to 0.179 ppm while Phosphate ranges from 0.084 to 0.106 ppm.